2010
DOI: 10.18632/aging.100127
|View full text |Cite
|
Sign up to set email alerts
|

A Two-tiered compensatory response to loss of DNA repair modulates aging and stress response pathways

Abstract: Activation of oxidative stress-responses and downregulation of insulin-like signaling (ILS) is seen in Nucleotide Excision Repair (NER) deficient segmental progeroid mice. Evidence suggests that this is a survival response to persistent transcription-blocking DNA damage, although the relevant lesions have not been identified. Here we show that loss of NTH-1, the only Base Excision Repair (BE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
37
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(42 citation statements)
references
References 55 publications
(85 reference statements)
5
37
0
Order By: Relevance
“…32,39 In our laboratory we have measured the mean lifespan of an unbiased population and found a 3-4 d reduced mean lifespan, but no reduction in maximum lifespan when the animals fed on OP50. 31 This result was independently confirmed in a collaborating laboratory which also showed that normal median lifespan was regained if we grow the same strain on E. coli HT115(DE3). 36 Hence, the lifespan of xpa-1 mutants is somewhat shorter than the isogenic wild-types, but it is influenced by external factors such as nutrition.…”
Section: Lifespan Of C Elegans Dna Repair Mutantsmentioning
confidence: 57%
See 4 more Smart Citations
“…32,39 In our laboratory we have measured the mean lifespan of an unbiased population and found a 3-4 d reduced mean lifespan, but no reduction in maximum lifespan when the animals fed on OP50. 31 This result was independently confirmed in a collaborating laboratory which also showed that normal median lifespan was regained if we grow the same strain on E. coli HT115(DE3). 36 Hence, the lifespan of xpa-1 mutants is somewhat shorter than the isogenic wild-types, but it is influenced by external factors such as nutrition.…”
Section: Lifespan Of C Elegans Dna Repair Mutantsmentioning
confidence: 57%
“…As expected from the near normal phenotype, xpa-1 mutants do not show the extensive transcriptomic modulation seen in segmental progeroid NER-defective mice. However, we, 31,36 and others, 51 identified a small yet informative set of genes differentially expressed in xpa-1 mutants. Gene set enrichment analyses (GSEA) revealed that the biological process (BP) "determination of adult lifespan" was the only overrepresented BP among the regulated genes.…”
Section: Hormesis Maintains Wildtype Phenotypes In Dna Repair Mutantsmentioning
confidence: 64%
See 3 more Smart Citations